Psychological Stress, Lung Function and Exacerbation Risk in COPD: Is an Increase of Cholinergic Tone a Possible Link?. (4th May 2018) - Liccardi, Gennaro; Calzetta, Luigino; Milanese, Manlio; Salzillo, Antonello; Manzi, Filippo; Ferrari, Marta; Rogliani, Paola
ABSTRACT: Summary at a glance: On the hypothesis that psychological distress might interfere with airway reactivity in patients suffering of mild to moderate COPD through a cholinergic-mediated-bronchial reflex.